Estudo de "Peixe Tipo" para projeto de escadas de peixe em barragens - Lourenço Filho, César Augusto (1975)
After general considerations, the rivers are specified how ecossystems. Some informations are given about the influence in the fishes by dams constructions and about methods of fishes protections, specially fish-ladders. Finally is introduced an original concept to fish-ladder design: the "fish-type".